PERFORMANCE GROWTH OF Kappaphycus alvarezii TISSUE CULTURE SEED WITH DIFFERENT WEIGHT - Cokrowati, Nunik; Sri Ismariani, Baiq; Nikmatullah, Aluh (Jurnal Perikanan Unram, 2019)
This study conducted to determine the effect of tissue culture seed weight on growth of Kappaphycus alvarezii and to determine the optimal weight. This study used a Completely Randomized Design (RAL) consisting of 4 treatments using with different seed weight. The treatment were P1: 50 gr, P2:75 gr, P3:100 gr, P4:125 gr. Treatments ware repeated 4 times (4 rafts). Data of obtained research variables od, be tabulated using excel microsof and be analyzed using analysis of variance and be continued tested by using Least Significant Difference (LSD) test. The highest weight gain result was obtained at weight of 125 gr and the highest growth rate at 50 gr, where in each of these treatments had an effect (p <0.05) seed weight on growth. This related to the competition of each individual seaweed in absorbing sunlight for photosynthesis. Weight of seed is one of the technical factors that can affect the growth of seaweed. Density in each seaweed bonds need to be so that it can cause seaweed fall.